CD163ΔSRCR5 MARC-145 Cells Resist PRRSV-2 Infection via Inhibiting Virus Uncoating, Which Requires the Interaction of CD163 With Calpain 1 - Yu, Piao; Wei, Ruiping; Dong, Wenjuan; Zhu, Zhenbang; Zhang, Xiaoxiao; Chen, Yaosheng; Liu, Xiaohong; Guo, Chunhe (Frontiers in Microbiology, 2020)
Porcine alveolar macrophages without the CD163 SRCR5 domain are resistant to porcine reproductive and respiratory syndrome virus (PRRSV) infection. However, whether the deletion of CD163 SRCR5 in MARC-145 cells confers resistance to PRRSV and interaction of which of the host proteins with CD163 is involved in virus uncoating remain unclear. Here we deleted the SRCR5 domain of CD163 in MARC-145 cells using CRISPR/Cas9 to generate a CD163ΔSRCR5 MARC-145 cell line. The modification of CD163 had no impact on CD163 expression. CD163ΔSRCR5 cells were completely resistant to infection by PRRSV-2 strains Li11, CHR6, TJM, and VR2332. The modified cells showed no cytokine response to PRRSV-2 infection and maintained normal cell vitality comparable with the WT cells. The resistant phenotype of the cells was stably maintained through cell passages. There were no replication transcription complexes in the CD163ΔSRCR5 cells. SRCR5 deletion did not disturb the colocalization of CD163 and PRRSV-N in early endosomes (EE). However, the interaction of the viral proteins GP2a, GP3, or GP5 with CD163, which is involved in virus uncoating was affected. Furthermore, 77 CD163-binding cellular proteins affected by the SRCR5 deletion were identified by LC-MS/MS. Inhibition of calpain 1 trapped the virions in EE and forced then into late endosomes but did not block viral attachment and internalization, suggesting that calpain 1 is involved in the uncoating. Overall, CD163ΔSRCR5 MARC-145 cells are fully resistant to PRRSV-2 infection and calpain 1 is identified as a novel host protein that interacts with CD163 to facilitate PRRSV uncoating.